2 Answers | Add Yours
y= (2-a)x + a
The equation is already in the slope for such that the slope m= (2-a) and b= a
==> To rewrite in b terms:
==> a= b
==> m= 2-a
==> m= 2- b
==> y= (2-b)x + b such that the slope m= (2-b).
Fortunately, the given equation: y = (2-a)x + a
is already set up in the required form: y = mx + b
Let us compare the two equations carefully; we find that
m = (2-a) and b = a
The equation y = mx + b represents graphically a straight line with the slope being m and the Y-intercept being b .
For the given equation, the slope m = (2-a) and the intercept b= a.
We’ve answered 396,489 questions. We can answer yours, too.Ask a question